ANALISIS PENALARAN ANALOGI SISWA KELAS XI MAN 1 POSO DALAM MATERI BARISAN GEOMETRI DITINJAU DARI GAAYA KOGNITIF - Basri, Risna; Rochaminah, Sutji; M, Bakri (Jurnal Elektronik Pendidikan Matematika Tadulako, 2022)
The objectives of this study are: (1) To describe the analogical reasoning of class XI MAN 1 Poso students in the material of geometric sequences from field independent cognitive style and field dependent cognitive style. This type of research is descriptive research using a qualitative approach. The subjects in this study were two students of class XI MIPA MAN 1 Poso even semester 2021/2022 consisting of one RM student with FI cognitive style and one FN student with FD cognitive style. The students' cognitive style data was obtained by giving the GEFT test, while the students' analogy reasoning data were collected from the analogy reasoning test and interviews. The results of this study indicate that (1) field independent cognitive style students' RM fulfills all stages in each indicator of analogical reasoning and can explain the analogy used, namely in the source and target problems there are similarities or analogies in the solution, namely using the nth term formula. in the geometric sequence, namely  so it is included in high analogical reasoning. (2) While the field dependent cognitive style students' FN tend to be less able to fulfill all stages of each indicator of analogical reasoning. At the applying stage, FN has not been able to apply the relational structure of the source problem in solving the target problem, and tends not to be able to explain the analogy used. because it can't explain the analogy used so FN is included in moderate analogy reasoning.